Effects of Long-Term Hepatic Ischemia-Reperfusion Injury on the Function of P-glycoprotein in vivo in Rats - Camilla A Thorling; Michael S Roberts; Xin Liu; Linda M Fletcher; Darrell Crawford; Frank J Burczynski (Frontiers Media S.A., 2014)
PURPOSE: Ischemia-reperfusion injury is a common complication in liver surgery with oxidative stress related graft failure as a potential complication. The oxidative stress could affect hepatic drug transporters such as P-glycoprotein, which is crucial in the hepatic clearance of certain immunosuppressant drugs. Thus,, it is important to study its function after ischemia-reperfusion injury in vivo. Rhodamine 123 is a fluorescent substrate of P-glycoprotein and its hepatic disposition can be visualized using multiphoton microscopy in vivo using anaesthetized animals. The aim of this study was to investigate the effect of long-term ischemia-reperfusion injury on P-glycoprotein function in hepatocytes using in vivo multiphoton microscopy. METHODS: Localized ischemia was induced for 1 hour in rats. The liver was reperfused for 4, 24, 48 hours or 1 week, where-after rhodamine 123 was injected intravenously. Multiphoton microscopy imaged the liver and bile was collected continuously up to 6 hours following drug administration. The liver was harvested for histology andprotein expression of P-glycoprotein. RESULTS: Ischemia-reperfusion injury resulted in extensive liver damage, inflammatory cell infiltration and apoptosis in the midzonal and centrilobular regions of the liver acinus. P-glycoprotein protein expression decreased. Cellular concentration of rhodamine 123 increased as visualized by multiphoton microscopy, which was confirmed with decreased excretion of rhodamine 123 in collected bile. CONCLUSIONS: This study showed reduced function of P-glycoprotein in ischemia-reperfusion injury as reflected by decreased biliary excretion of Rhodamine 123, as well as reduced protein expression of the transporter. Multiphoton microscopy could be used to visualize and quantitate the intracellular levels of rhodamine 123. These findings stipulate the importance of using multiphoton microscopy to understand transmembrane drug flux and reflect on careful drug dosing after hepatic surgery.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.